Development of the adaptive spring bread wheat cultivar ‘Omskaya Yubileynaya’ under the conditions of the Siberian region - N. A. Popolzukhina; P. V. Popolzukhin; A. A. Gaidar; Yu. Yu. Parshutkin; N. A. Yakunina (Труды по прикладной ботанике, генетике и селекции)
Background. As reported by the Russian Federal State Statistics Service, spring bread wheat planting acreage in 2019 reached 48% (28 million ha) of the total crop area in Russia. About 20% (5.4 million ha) of spring wheat was cultivated in the Siberian region. This is the reason why the region plays an important role in wheat cultivation, and the development of highly efficient cultivars adapted to Siberian environments is one of the prioritized tasks in the efforts to obtain sustainable spring bread wheat harvests.Materials and methods. Mutants and mutant × cultivar hybrids were used as parent material for top crossing. A decision was taken to apply multifold individual selection in accordance with the composition of agronomic traits in the mutant × cultivar hybrid population Lutescens 3 × [F5 B1 (Mutant 777 × G7251/03) × G7251/03] × Rosinka 3 (Mutant 112 × Irtyshanka 10) with backcrossing. In 2001–2016, expe rimental work was conducted at Omsk Agrarian Scientific Centre. Environmental testing was carried out at the Stepnoy Experiment Station (the steppe zone of Omsk Province) and the A.I. Barayev Research and Production Centre for Grain Farming (Northern Kazakhstan). The experiments and observations were performed in accordance with the techniques recommended by the State Commission for Crop Variety Trials.Results. The research showed that cv. ‘Omskaya Yubileynaya’ was characterized by resistance to lodging and to major plant diseases. It exceeded the reference in grain yield both in fallow (+0,50 t/ha) and nonfallow lands (+0,58 t/ha). The distinguishing feature of this cultivar was its large grain of high quality.Conclusions. During the development of cv. ‘Omskaya Yubileynaya’, the data were obtained that justified its prospective cultivation within the steppe and forest-steppe zones of Siberia and Kazakhstan. The cultivar has been registered in the national lists of breeding achievements since 2019.